PENGARUH JUMLAH KUNJUNGAN WISATAWAN DAN TINGKAT HUNIAN HOTEL PAD DAN TINGKAT PENGANGGURAN DI PROVINSI BALI - Rasa, I Wayan Angga Purna; Yasa, I Nyoman Mahaendra (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2022)
Bali Province is one of the popular tourist destinations for tourists. Various things are done by the government to maintain the existence of tourism in the Province of Bali. The quality of human resources is a reflection of the welfare of the community as seen from the decline in the unemployment rate. The purpose of this study was to analyze the influence of the number of tourist visits and hotel occupancy rates on PAD and unemployment rates in Bali Province. This research is sourced from time series data 1998-2018. The analysis technique used is the path analysis technique. The results of data analysis showed that the number of tourist visits had a positive and significant effect, while hotel occupancy rates had a positive but not significant effect on the PAD of Bali Province. The number of tourist visits and hotel occupancy rates have a negative and significant effect, while the PAD has no negative and significant effect on the unemployment rate of Bali Province. The number of tourist visits has an indirect effect on the unemployment rate through local own-income in the Province of Bali. Keywords : number of tourist visits, hotel occupancy rates, local original income, and unemployment rates.